Pengaruh Pemberian Ekstrak Etanol Buah Masisin (Rhodomyrtus tomentosa Wight) terhadap Frekuensi, Konsistensi, dan Durasi Diare pada Hewan Coba Mencit Putih Jantan (Mus musculus) yang Diinduksi Oleum Ricini - Angeline Novia Toemon; Austin Bertilova Carmelita; Astri Widiarti; Dian Mutiasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
People in Central Borneo which is often used to treat diarrhea is the fruit of masisin (Rhodomyrtus tomentosa Wight) with active compounds which are capable to treat diarrhea such as alkaloids, flavonoids, tannins, saponins, and steroids. Diarrhea is a defecate with a liquid or half-liquid feces, the content of water in a feces is more than usual, it is more than 200 g or 200 ml / 24 hours. To know the effectiveness of the extract of the fruit of masisin as an alternative to antidiarrheal treatment seen from the frequency, duration, and consistency of feces in male white mice (Mus musculus). This study design was a true experimental design with post-test control group design with 5 treatments for each group. This study started by making some extracts of Masisin fruit. Followed observation with 5 treatment groups animals. The induction of diarrhea was using oleum ricini, with aquadest as the negative control, and Loperamide HCL as the positive control. The dose of ethanol extracts of masisin fruit divided into 0.3 mg/g BW, 0.6 mg/g BW and 1.2 mg/g BW, all of the treatments were given orally. This study data was statistically analyzed with one way ANOVA. The results of one way ANOVA test showed that the value of p <0,05 meaning that there is the influence of EEBM on frequency, consistency and duration of diarrhea at doses 0.3 mg/g BW, 0.6 mg/g BW and 1.2 mg/Gbw. Based on observations ethanol extracts of masisin fruit had antidiarrheal effect at doses 0,3 mg/g BW, 0.6 mg/g BW and 1.2 mg/g BW in male white mice (Mus musculus).